Cross-Cultural Religious Literacy and Faith-Based Social Service Organizations’ Boards - Summers, Stephanie (The review of faith & international affairs, 2024)
A growing body of literature provides insight on the importance of education for cross-cultural religious literacy. Yet for many faith-based social service organizations, one area where such education is underdeveloped is at the board table. This essay recommends key practices for the boards of faith-based social services organizations intending to grow in their understanding of cross-cultural religious literacy.